The Temporal Effects of Divorces and Separations on Children’s Academic Achievement and Problem Behavior - Arkes, Jeremy (J Divorce Remarriage, 2014)
This paper provides an examination of the effects of the divorce and separation process on children’s academic achievement over time. By using child fixed effects and establishing a baseline period that is 4-or-more years prior to a family disruption, I can examine how children are affected in different periods relative to the disruption and whether any negative effects subside, persist, or escalate as time passes from the disruption. With a sample of 7-14 year olds, I find: children are affected at least 2-4 years before the disruption; reading test scores are most affected; and for Reading Comprehension, the negative effects persist and even escalate as time passes from the disruption.